Liver steatosis is a risk factor for hepatotoxicity in inflammatory bowel disease patients treated with azathioprine. Issue 10 (October 2020) - Phillips, Jennifer; Preskey, Rebecca; Penfold, Chris; Gordon, Fiona; Tyrrell-Price, Jonathan
Abstract : Background and aims: The literature demonstrates that hepatic steatosis reduces the tolerance of immunosuppression in people with inflammatory bowel disease. It also shows that elevated methylmercaptopurine may be responsible for thiopurine-induced hepatitis. This exploratory study investigates the relationship between hepatic steatosis, methylmercaptopurine and alanine transaminase. Methods: We performed a retrospective review of patients started on azathioprine treatment at University Hospitals Bristol NHS Foundation Trust between 2014 and 2017. There were 600 patients in total. Ninety-one patients met our inclusion criteria which were at least one ultrasound scan commenting on the appearance of the liver, liver function tests at commencement of azathioprine and liver function tests and a methylmercaptopurine level between 6 and 8 weeks after starting treatment. Results: Of 91 patients included in our study, 32 patients (32%) were identified as having radiological hepatic steatosis on ultrasound imaging and 59 patients had no evidence of steatosis. We found a positive association between methylmercaptopurine levels and change in alanine transaminase in patients with hepatic steatosis ( P < 0.001) but not in those with a normal liver on ultrasound imaging. Conclusion: We conclude that the higher levels of methylmercaptopurine may be a risk factor for hepatitis in patients with hepatic steatosis but not in those with a normal liver.